Learning Through Play at School – A Framework for Policy and Practice - Parker, Rachel; Thomsen, Bo Stjerne; Berry, Amy (Frontiers in Education, 2022)
Learning through play has emerged as an important strategy to promote student engagement, inclusion, and holistic skills development beyond the preschool years. Policy makers, researchers and educators have promoted the notion that learning though play is developmentally appropriate – as it leverages school-age children’s innate curiosity while easing the often difficult transition from preschool to school. However, there is a dearth of evidence and practical guidance on how learning through play can be employed effectively in the formal school context, and the conditions that support success. This paper addresses the disconnect between policy, research and practice by presenting a range of empirical studies across a number of well-known pedagogies. These studies describe how children can foster cognitive, social, emotional, creative and physical skills through active engagement in learning that is experienced as joyful, meaningful, socially interactive, actively engaging and iterative. The authors propose an expanded definition for learning through play at school based on the science of learning, and summarise key findings from international studies on the impact of children’s learning through play. They identify four key challenges that underpin the considerable gap between education policy and practice, and propose a useful framework that addresses these challenges via a common language and structure to implement learning through play.